A note on generalizations of Bailey's identity involving products of generalized hypergeometric series - Kilicman, Adem; Kurumujji, Shantha Kumari; Rathie, Arjun K. (Korean Mathematical Society, 2022)
In the theory of hypergeometric and generalized hypergeometric series, the well-known and very useful identity due to Bailey (which is a generalization of the Preece's identity) plays an important role. The aim of this research paper is to provide generalizations of Bailey's identity involving products of generalized hypergeometric series in the most general form. A few known, as well as new results, have also been obtained as special cases of our main findings.